Spatiotemporal variation of high-temperature events and its relation to coral bleaching in the Ryukyu Islands, Japan - Sayaka Yasunaka; Haruko Kurihara; Takeshi Doi (Progress in Earth and Planetary Science)
Abstract Coral bleaching occurs when symbiotic dinoflagellate algae leave corals due to warming surface waters. Since the early 1980s, the number and intensity of coral bleaching events have significantly risen globally, and many coral reefs are concerned to undergo irreversible phase shifts due to global warming. In this study, we examine spatiotemporal variations and relationships of high-temperature events, high-temperature anomaly events, and coral bleaching around the Ryukyu Islands, Japan. We also explore the correlation between these occurrences and the large-scale climate variability, El Niño–Southern Oscillation and Indian Ocean Dipole. More than 99% of the high-temperature events occurred from June to October, and more than 80% occurred from July to September, whereas high-temperature anomaly events occurred all year round. Corresponding with high-temperature events, more than 10% of the data reported overall bleaching, and more than 25% reported partial bleaching from June to October. Over 40% of data reported bleaching in August, of which 50% of these reports were categorized as overall bleaching and the remainder as partial. The spatial distribution of coral bleaching also corresponded better with high-temperature events than high-temperature anomaly events. In 2016, extensive and severe coral bleaching was reported around the Okinawa, Miyako, and Yaeyama Islands, where intense high-temperature events had occurred. The central-to-eastern equatorial Pacific displayed a negative sea surface temperature anomaly, and the eastern Indian Ocean did a positive anomaly following high-temperature events near the Ryukyu Islands. These findings indicated that the high-temperature events around the Ryukyu Islands show correlation with La Niña and a negative Indian Ocean Dipole. If the cumulative temperature of high-temperature events exceeds 56 °C-days every three years in the late 2030s, then the corals around the Ryukyu Islands will suffer high mortality within 20 years.